(untitled) (Revista Científica Compendium, 2021)
Ecuadorian mango is a potentially competitive fruit due to comparative advantages such as soil and climate that are excellent for cultivation and growth. In the literature review, mango is presented in its types, pests that affect it, and volumes of dollars and tons of exports. The methodology used is a descriptive and exploratory quantitative approach that relates the variables international competitiveness and mango value chain by constructs; hypotheses about a significant relationship between the variables were tested; the results showed that such relationship exists, so it was concluded that in order to achieve international competitiveness, the mango value chain must focus on the links between stakeholders, in the maximum exploitation of the fruit and the added value that can be given to the fruit, as well as promote research and innovation.